2011
DOI: 10.5761/atcs.cr.10.01619
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exacerbation of Idiopathic Pulmonary Fibrosis of Microscopic Usual Interstitial Pneumonia Pattern after Lung Cancer Surgery

Abstract: A 78-year-old man underwent right lower lobectomy for lung cancer. Histopathological examination led to the diagnosis of adenosquamous cell carcinoma. The background lung adjacent to the pleura showed idiopathic pulmonary fibrosis of microscopic usual interstitial pneumonia pattern, although preoperative computed tomography showed no apparent findings of interstitial pneumonia. The patient showed an acute exacerbation of idiopathic pulmonary fibrosis on the third postoperative day. We herein report a case of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Furthermore, neither drug has been tested prospectively in patients with coexisting IPF and lung cancer [8]. In previous studies, 22% of patients with IPF developed primary lung cancers, corresponding with a five-fold greater risk than that in the general population [8,9,10,11,12]. Similarly, primary lung cancer risk is more than 20 times higher in patients who undergo lung transplantation for IPF than in the general population [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neither drug has been tested prospectively in patients with coexisting IPF and lung cancer [8]. In previous studies, 22% of patients with IPF developed primary lung cancers, corresponding with a five-fold greater risk than that in the general population [8,9,10,11,12]. Similarly, primary lung cancer risk is more than 20 times higher in patients who undergo lung transplantation for IPF than in the general population [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…AE-IPF has also been observed in patients receiving chemotherapy for lung cancer, or following radiotherapy (Sakamoto et al, 2011;Goto et al, 2011;Watanabe et al, 2011). Minegishi et al reported that AE developed after chemotherapy (single drug: 20%, multiple drugs: 42.9%) and radiation therapy (16.7%), but also occurred in 20% of the patients who received only supportive care without any therapy (Minegishi et al, 2009).…”
Section: Drugsmentioning
confidence: 99%
“…We previously reported a patient who showed AE of microscopic UIP after lung cancer surgery ( Figure 1 ). Even such a microscopic UIP pattern may become exacerbated after chest surgery [ 26 ].…”
Section: Pathology Of the Microscopic Usual Interstitial Pneumoniamentioning
confidence: 99%
“…( C , D ) The arrow indicates active fibroblastic foci ( A , C , Hematoxylin and eosin staining; B , D , Elastica-van Gieson staining). This figure is adapted from Goto T. Ann Thorac Cardiovasc Surg (2011) 17, 573–576 [ 26 ].…”
Section: Figurementioning
confidence: 99%